The Relevance of Folklore in an Indigenous Language Teaching and Learning Situation: The Case Study of Sepedi - Maruma, Mamalatswa W.; Molotja, Tsebe W. (Southern African Journal for Folklore Studies, 2018)
The article highlights folklore as an effective and genuine tool for indigenous language teaching and learning in the 21st century. There is a need to use pure, error-free and standardised language for it to be acknowledged and respected. In the campaign to sustain and preserve the revived indigenous languages—in this case, Sepedi—employing folk narratives in a text-based approach in teaching and learning Sepedi can develop in learners the desire to use language that is more refined, literary, figurative, symbolic and deep in meaning. Document study was adopted as the research method in this inquiry. Folk narratives in Moepathutse by Makopo were explored as they are rich in vocabulary and culture and promote indigenous knowledge. The study revealed that: a) Sepedi folk narratives are rich in relevant Sepedi vocabulary, b) employing folk narratives in a text-based approach results in teaching and learning the language in context and c) folk narratives preserve culture. The study recommends that language teachers promote and conserve indigenous languages through the use of folklore in a text-based approach. This is because folklore enhances relevant vocabulary. Furthermore, folklore supports languages to be learned in context – it is therefore, in the use of folk narratives that ethos, values, traditions, and cultures are preserved in communities. The study therefore, concludes that folklore is a relevant tool through which indigenous languages can be instilled and preserved by language users.
Article published in the Southern African Journal for Folklore Studies Volume 28 Number 1 2018 #4293 11 pages
Keywords: Folklore; Folk narratives; Indigenous languages; Learner-centred pedagogy; Teaching-learning situation; Text-based approach; Folklore and education; Indigenous people--Languages